Effects of Service Quality Characteristics of the 2018 Webtoon Lore Olympus on User Satisfaction and Reuse Intention of Generation Z in Korea - Kang, Austin SH; Seo, YS; Kim, Hyo (Journal Communication Spectrum: Capturing New Perspectives in Communication, 2023)
This study was conducted to examine the Generation Z’s satisfaction and reuse intention of the service factors of the webtoon Lore Olympus in Korea. We examined the satisfaction and reuse intentions of Generation Z users who received the service of the US webtoon Lore Olympus at Korean portal site Naver from July 1 to July 31, 2022. Results show that the entertainingness and design characteristics of Lore Olympus significantly affected on Generation Z’s satisfaction and reuse intention in Korea. User satisfaction also affected reuse intentions. The webtoon service factors such as entertainingness and design characteristics of Lore Olympus were confirmed to have an effect on Generation Z’s satisfaction and reuse intention in Korea. To cite this article (7th APA style): Seo, Y. S., Kang, A. & Kim, H. (2023). Effects of Service Quality Characteristics of the 2018 Webtoon Lore Olympus on User Satisfaction and Reuse Intention of Generation Z in Korea. Journal Communication Spectrum: Capturing New Perspectives in Communication 13(1), 1-12. http://dx.doi.org/10.36782/jcs.v13i1.2100